A Cluster Randomized Evaluation of a Health Department Data to Care Intervention Designed to Increase Engagement in HIV Care and Antiretroviral Use. Issue 6 (June 2018) - Dombrowski, Julia C.; Hughes, James P.; Buskin, Susan E.; Bennett, Amy; Katz, David; Fleming, Mark; Nunez, Angela; Golden, Matthew R.
Abstract : Background: Many US health departments have implemented Data to Care interventions, which use HIV surveillance data to identify persons who are inadequately engaged in HIV medical care and assist them with care reengagement, but the effectiveness of this strategy is uncertain. Methods: We conducted a stepped-wedge, cluster-randomized evaluation of a Data to Care intervention in King County, Washington, 2011 to 2014. Persons diagnosed as having HIV for at least 6 months were eligible based on 1 of 2 criteria: (1) viral load (VL) greater than 500 copies/mL and CD4 less than 350 cells/μL at the last report in the past 12 months or (2) no CD4 or VL reported to the health department for at least 12 months. The intervention included medical provider contact, patient contact, and a structured individual interview. Health department staff assisted patients with reengagement using health systems navigation, brief counseling, and referral to support services. We clustered all eligible cases in the county by the last known medical provider and randomized the order of clusters for intervention, creating contemporaneous intervention and control periods (cases in later clusters contributed person-time to the control period at the same time that cases in earlier clusters contributed person-time to the intervention period). We compared the time to viral suppression (VL <200 copies/mL) for individuals during intervention and control periods using a Cox proportional hazards model. Results: We identified 997 persons (intention to treat [ITT]), 18% of whom had moved or died. Of the remaining 822 (modified ITT), 161 (20%) had an undetectable VL reported before contact and 164 (20%) completed the individual interview. The hazard ratio (HR) for time to viral suppression did not differ between the intervention and control periods in ITT (HR, 1.21 [95% confidence interval, 0.85–1.71]) or modified ITT (HR, 1.18 [95% confidence interval, 0.83–1.68]) analysis. Conclusions: The Data to Care intervention did not impact time to viral suppression. Abstract : A randomized controlled evaluation of a health department Data to Care intervention found that the strategy did not impact viral suppression or relinkage to care among persons with evidence of poor engagement in HIV care.Supplemental digital content is available in the text.